10 MW mechanical power transfer standard for nacelle test benches using a torque transducer and an inclinometer. (December 2021) - Song, Zihang; Weidinger, Paula; Eich, Norbert; Zhang, Hongkun; Yogal, Nijan; Kumme, Rolf
Abstract: Accurately measuring the mechanical power of wind turbines is essential for determining their efficiencies. As there is currently no standardized method available for a traceable mechanical power measurement of wind turbines, we propose a 10 MW mechanical power transfer standard based on a 5 MN·m torque transducer and an inclinometer for rotational speed measurements up to 20 min −1 . In particular, the deviation of using an inclinometer is investigated both in simulation and experiments, and a compensation method is proposed. By tracing both the torque and the rotational speed measurements to national standards, it can offer a mechanical power measurement with 0.5 % measurement uncertainty.